Food healthiness versus tastiness: Contrasting their impact on more and less successful healthy shoppers within a virtual food shopping task - Mergelsberg, E.; MacLeod, C.; Mullan, Barbara; Rudaizky, D.; Allom, Vanessa; Houben, K.; Lipp, Ottmar (Elsevier BV, 2019)
A virtual shopping task was employed to illuminate why women who intend to shop healthily are differentially successful in doing so. Female undergraduates (N = 68) performed a modified approach and avoidance task that employed food items differing in healthiness and tastiness, and yielded relative speed to select and reject food items in a stylised supermarket. Participants categorised a food item either in terms of healthiness or tastiness, then pulled (selected) or pushed (rejected) the item using a joystick. Participants showed faster selection of tasty food after categorisation in terms of tastiness, irrespective of the food's healthiness. However, after categorisation in terms of healthiness, only more successful healthy food shoppers showed faster selection of healthy items regardless of tastiness. Less successful healthy food shoppers showed this effect only for tasty food, and displayed faster rejection of food items not considered tasty, regardless of their assessed healthiness. Thus, when participants who reported the greatest gap between their shopping intention and shopping behaviour were judging the healthiness of food items, their speed to select and reject items continued to be influenced by tastiness. This suggests that reducing incidental processing of food tastiness may reduce the intention-behaviour gap in healthy food shopping.